Odpowiedzi

Najlepsza Odpowiedź!
2010-03-31T16:18:41+02:00
A). x²-7x+12>0
Δ=b²-4ac = 49-48=1
x=(-b+√Δ)/2a = 7+1 / 2=8/2=4
x=(-b-√Δ)/2a = 7-1 / 2=6/2=3
x∈(-∞;3)U(4;+∞)

b). (x-3)( x²-x-2)≤0
x=3
Δ=b²-4ac=1+8=9
x=(-b+√Δ)/2a = 1+3 / 2 = 4/2 = 2
x=(-b-√Δ)/2a = 1-3 / 2 = -2/2 = -1
x∈(-∞;-1>U<1;3>

c). x³+2x²-13x+10>0
Dzielnik 1, bo 1³+2*1²-13*1+10=0, czyli (x-1)
(x³+2x²-13x+10):(x-1)=x²+3x-10
stąd mamy
(x²+3x-10)(x-1)>0
Δ=b²-4ac=9+40=49
x=(-b+√Δ)/2a = -3+7 / 2 = 4/2 = 2
x=(-b-√Δ)/2a = -3-7 / 2 = -10/2 = -5
x=1
x∈(-5;1)U(2,+∞)
2010-03-31T16:48:05+02:00
X^2-7x+12>0
x²-7x+12>0

Δ=b²-4ac
Δ=49-4*1*12
Δ=49-48
Δ=1
√Δ=1

x₁=-b-√Δ / 2a
x₁=7-1/2
x₁=3

x₂=-b+√Δ / 2a
x₂=7+1 / 2
x₂=4

x₁=3 x₂=4 (jeśli rysujesz na osi, kółka puste, ramiona do góry i zaznaczasz x>0)



(x-3)( x²-x-2)≤0

x₁=3

x²-x-2≤0
Δ=-b+√Δ / 2a
Δ=1-4*(-2)
Δ=1+8
Δ=9
√Δ=3

x₂= -1

x₃= 2

(na osi:ramiona w góre,kółka zamalowane, x<0)